Unmet needs in the management of psoriasis in Latin America: a systematic review - Bruna Ossanai Schoenardie; Rodrigo Oliveira Almeida; Thaísa Hanemann; Arthur Ossanai Schoenardie; André Lucas Ribeiro; Juliana Catucci Boza (Sociedade Brasileira de Dermatologia, 2024)
Abstract Background Psoriasis is a chronic, systemic inflammatory disease with a worldwide prevalence of approximately 2%. Currently, despite the difficulties faced every day by patients and physicians in low-resource countries, literature describing the exact needs of psoriasis treatment in Latin America remains scarce. Objective To investigate the unmet needs in psoriasis treatment in Latin America. Methods The authors conducted a systematic review following PRISMA statements in PubMed, Embase, and LILACS of studies published from January 2011 to March 2021 addressing challenges in psoriasis treatment in Latin America. Results The search strategy identified 3,837 articles, of which 19 were included in the final analysis. Most were from Brazil (58%; n = 11), all were observational, and most were cross-sectional (84%; n = 16). Difficulties faced by psoriasis patients in Latin America included the high prevalence of opportunistic and endemic infections (42% of the studies addressed this matter; n = 8), delay in diagnosis (5%; n = 1), work productivity impairment (16%; n = 3), limited access to medication/medical care (37%; n = 7), poor adherence to treatment (5%; n = 1) and poor adherence to guidelines (11%; n = 2). Study limitations Number and quality of studies currently available on this subject. Conclusions Current psoriasis guidelines do not always account for epidemiological, financial, and cultural characteristics. Most studies available are from Brazil, which might not accurately represent Latin America as a whole. In a region where neglected diseases and scarce resources remain a reality, it is imperative that dermatological training be offered to primary care providers, allowing for standardized conduct and earlier diagnosis.